2008
DOI: 10.1136/sti.2008.030973
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported syphilis and gonorrhoea testing among men who have sex with men: national HIV behavioural surveillance system, 2003-5

Abstract: Syphilis and gonorrhoea testing among MSM was low, despite specific testing recommendations in the STD treatment guidelines. To increase STD testing among MSM, healthcare providers should assess the risks of STD for male patients through routine enquiries about sexual activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
15
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 19 publications
1
15
2
Order By: Relevance
“…Compared to our finding of syphilis screening rates of 66.0% to 75.8% and gonorrhea screening rates of 3.0% to 18.3%, a study of self-reported STD testing among HIV-negative MSM during 2003-2005 found lower rates for syphilis (39%) but higher rates for gonorrhea (36%). 22 Several factors can account for our finding of higher screening rates for syphilis than for chlamydia or gonorrhea. Providers were probably aware that untreated syphilis can result in adverse health outcomes, with infection resulting in neurologic or ophthalmic manifestations, and that syphilis infection increases HIV viral load and decreases CD4 cell count in HIV-infected persons, thereby increasing the risk of transmitting HIV.…”
Section: Discussionmentioning
confidence: 89%
“…Compared to our finding of syphilis screening rates of 66.0% to 75.8% and gonorrhea screening rates of 3.0% to 18.3%, a study of self-reported STD testing among HIV-negative MSM during 2003-2005 found lower rates for syphilis (39%) but higher rates for gonorrhea (36%). 22 Several factors can account for our finding of higher screening rates for syphilis than for chlamydia or gonorrhea. Providers were probably aware that untreated syphilis can result in adverse health outcomes, with infection resulting in neurologic or ophthalmic manifestations, and that syphilis infection increases HIV viral load and decreases CD4 cell count in HIV-infected persons, thereby increasing the risk of transmitting HIV.…”
Section: Discussionmentioning
confidence: 89%
“…Adherence to these screening recommendations is an important strategy for gonorrhea control in sexually active MSM, because asymptomatic infection at pharyngeal and rectal sites is common among this population, and gonococcal transmission is efficient with insertive or receptive rectal intercourse and fellatio [11]. Despite these recommendations, in surveys of sexually active MSM who attend venues frequented by MSM, 36% self-reported being tested for gonorrhea in the past year [13].…”
mentioning
confidence: 98%
“…[13][14][15]42 Studies also suggest that MSM may not screen for HIV and STDs due to perceived low risk for infection and fear of a positive result, as well as concerns over test access, affordability, and confidentiality. 15,19,[43][44][45] Few studies to date, however, have examined HIV and STD testing with exclusively Black MSM samples.…”
mentioning
confidence: 99%
“…Data from the National HIV Behavioral Surveillance System demonstrated that among a venue-based sample of 10,030 MSM, 39% and 36% had been tested for syphilis and gonorrhea in the past year, respectively. 13 Johnson and colleagues 14 found that whereas 81% of MSM has been recently tested for HIV, only 61% had been screened for STDs. Similar results were found in another sample of MSM in Massachusetts.…”
mentioning
confidence: 99%